Formación profesional obrera. Instrucción militar e ideológica en la Fábrica Nacional de Trubia (Asturias) (Estudios humanísticos. Geografía, historia y arte, 1996)
The Arms Factory in Trubia was one of the most important industrial trading centres in the region. It pioneered the introduction of advanced techniques in iron and steel works. It was there that the second professional training centre the world was formet. It is to this respect that we dedicate the present article, emphasizing the importante of the origin, objetives and development of the worhers training school in Trubia from 1850 to 1977, the year of it's closure.